2022
DOI: 10.3389/fpsyg.2022.896505
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Effects of Stressors on Task Performance: The Role of Thriving at Work and Resilience

Abstract: This study unveils the effects of stressors on employees' task performance through the mediating role of thriving at work (TAW) and a moderating role of resilience (RES) grounding on conservation of resources (COR) theory. The analysis of collected data from 331 supervisor-employee dyads in the hospitality sector of China explicates that the role conflict (RC) and perceived workload have a negative influence on TAW, and thriving has a positive relationship with task performance. The results corroborate the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…Thus, H2 was accepted. As expected, this finding agrees with the position of previous studies (Ali et al, 2018;Elahi et al, 2019;Hussain et al, 2022) that reported the same positive and significant thriving-JP relationship. This finding affirmed the arguments drawn from the socially embedded model of thriving that thriving influences employees' adaptive functioning to enable them to achieve better JP.…”
Section: Findings and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, H2 was accepted. As expected, this finding agrees with the position of previous studies (Ali et al, 2018;Elahi et al, 2019;Hussain et al, 2022) that reported the same positive and significant thriving-JP relationship. This finding affirmed the arguments drawn from the socially embedded model of thriving that thriving influences employees' adaptive functioning to enable them to achieve better JP.…”
Section: Findings and Discussionsupporting
confidence: 93%
“…The formation of a positive psychological state enables them to develop additional work resources to fuel behaviours necessary for optimal functioning and performance improvement. Thriving association with JP has been confirmed in previous empirical studies (Ali et al, 2018;Elahi et al, 2019;Hussain et al, 2022). More so, thriving has been operationalised as an intermediary construct in studies involving work behaviour(s) and JP.…”
Section: Mediating Role Of Thriving Between Social Media Use and Job ...mentioning
confidence: 55%
See 1 more Smart Citation